Relationship between Addiction to Online Video Games and Cognitive Function in Adolescents - Imran, Yudhisman; Putri, Dian Maharani (CoinReads Media Prima, 2024)
Introduction: Adolescent is a particular transition phase especially in their development of cognitive function. Cognitive interpreted as an activity of brain which has a function to its external environment. In Pasific Asia, the prevalence of people with decreased cognitive function is 6,7%. One of the factors contributes to this problem is playing online video game. Many previous researches have analyzed the correlation between online video games and cognitive function but there is still pros and cons about this. The aim of this study is to assess the relationship between addiction to online video games and cognitive function in adolescents. Method: The method used in this study is a cross-sectional design of 56 adolescents who were selected using consecutive non-random sampling and met the inclusion criteria. Online video game addiction data is obtained from game addiction scale (GAS) questionnaire and Montreal Cognitive Assessment (MOCA-INA) is used to assess cognitive function. The relationship between two variables were analyzed using the Fisher's Exact. Results: From 56 respondents, 44,6% experienced a decrease in their cognitive function. Data shows the lowest score of domain are attention (64.3%) and memory (55.4%). The respondents who are addicted to online video games are 16.1%. Conclusion: In this study, there is no relationship between addiction to online video games and cognitive function in adolescents.